Tinjauan Hukum Internasional dalam Menangani Kasus Piracy Jure Gentium Berdasarkan Yurisdiksi Universal - Putri Rizka Nurwijedah Kadir; Darwis Darwis; Imam Fadhil Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study discusses the application of universal jurisdiction in addressing piracy jure gentium based on international law. Universal jurisdiction allows a country to prosecute perpetrators of serious crimes, such as piracy, regardless of the crime's location or the nationality of the perpetrator and victim. Rooted in customary international law, which recognizes piracy as a threat to the collective interests of all nations, every country has the right and obligation to act against pirates. This research employs a normative legal approach, focusing on analyzing relevant international legal regulations. The findings indicate that the international legal framework, particularly the United Nations Convention on the Law of the Sea (UNCLOS), provides guidance for enforcing laws against piracy. However, while the principle of universal jurisdiction offers a solution, challenges such as a lack of international consensus on the definition of piracy, resource limitations in developing countries, and the need for stronger international cooperation hinder its implementation. This study emphasizes the importance of inter-state cooperation, including support from developed countries to developing nations, to enhance law enforcement capacity. Moreover, the application of universal jurisdiction contributes to international justice, where consistent law enforcement reflects the international community's commitment to protecting maritime safety and global trade. Thus, this research aims to provide a comprehensive understanding of the application of universal jurisdiction in the context of piracy in international waters and its implications for the overall international legal system.